Estratégias de enfrentamento à violência contra a mulher: uma avaliação do setor de autonomia econômica da casa da mulher brasileira do Ceará - Rodrigues, Rachel de Mesquita (2024)
The Casa da Mulher Brasileira do Ceará (CBM-CE) has the Economic Autonomy Sector, which aims to expand the insertion of women in situations of violence in the job market and the generation of income, through the offer of professional qualifications and education continued. It turns out that, in order to break the cycle of violence, in addition to financial independence, women also need to gain emotional independence, since they can only enter and remain in the job market if they are psychologically well. In this context, the Sector, through partnerships, also promotes group therapeutic activities, aimed at the emotional development of the women assisted, thus combining professional, personal and social strategies. The objective of this work is to evaluate the social promotion strategies of the Economic Autonomy Sector for women victims of domestic violence, users of the Casa da Mulher Brasileira in Ceará, in the development of their independence. The study is supported by In-Depth Assessment and its four axes, opting for a qualitative and interpretative approach, through bibliographic, documentary and field studies, investigating the perception of users and professionals at the House in relation to the object of study. For the theoretical basis, feminist authors who discuss work and violence against women are used. In the field research, semi-structured interviews were carried out with professionals from the Economic Autonomy Sector and with the women assisted by CMB-CE, who are monitored by them. The documentary and bibliographic analysis found a drop in the budget for public policies for women, with 2019 being the year with the lowest budget allocated to policies for women's economic autonomy. During field research, it was observed the need for emotional and psychological strengthening work, before or concomitantly with the participation of women victims of violence in professional courses offered by the Economic Autonomy Sector of CMB-CE. Otherwise, that is, without this support, those assisted seek to take one course right after another, without, however, being able to enter the job market or, even, when they do manage to do so, they do not stay there for a long time, due to lack of resources. emotional structure.